2021
DOI: 10.1016/j.jval.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation in Opioid Modeling: Systematic Review

Abstract: The rapid increase in opioid overdose and opioid use disorder (OUD) over the past 20 years is a complex problem associated with significant economic costs for healthcare systems and society. Simulation models have been developed to capture and identify ways to manage this complexity and to evaluate the potential costs of different strategies to reduce overdoses and OUD. A review of simulation-based economic evaluations is warranted to fully characterize this set of literature.Methods: A systematic review of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Both Mueller et al [13] and Chao and Loshak [12] focused mainly on effectiveness but concluded that community distribution of naloxone was cost effective based on the limited studies included in their reviews. Most recently, Beaulieu et al [14] performed a systematic review of model-based cost-effectiveness studies for a variety of interventions to address opioid use disorder, one of which was distribution of naloxone to laypeople. They concluded that community distribution of naloxone was cost effective.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Mueller et al [13] and Chao and Loshak [12] focused mainly on effectiveness but concluded that community distribution of naloxone was cost effective based on the limited studies included in their reviews. Most recently, Beaulieu et al [14] performed a systematic review of model-based cost-effectiveness studies for a variety of interventions to address opioid use disorder, one of which was distribution of naloxone to laypeople. They concluded that community distribution of naloxone was cost effective.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…Trialbased cost-effectiveness studies are useful in verifying in realworld contexts the assumptions made in models. Additionally, our review updates the search of the literature by about a year and conducts a more thorough critical appraisal [14].…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…Medicaid government assistance programs that fund health care coverage for eligible low-income individuals and vary from state to state, could benefit substantially from economic evaluations given the considerable population health and financial burden that the treatment of OUD and co-occurring mental health disorders places upon them ( Leslie et al, 2019 ). However, to date, only a handful of studies have explicitly sought to investigate the cost-effectiveness of OUD interventions from the perspective of a state Medicaid program ( Beaulieu et al, 2021 ; Onuoha et al, 2021 ). In addition to state Medicaid programs, local health departments (LHDs), which are responsible for surveillance and prevention activities, play a crucial role in responding to opioid use and overdose within their own communities (often at county-level) ( Evans et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2011 and 2016, caseloads involving the children and adolescents whose parents were affected by OUD were estimated to cost the US Child Welfare $2.8 billion ( Crowley et al, 2019 ). Existing studies in OUD illustrate that non-health costs can be incorporated in economic evaluations ( Beaulieu et al, 2021 ; Onuoha et al, 2021 ). However, these studies have tended to aggregate health and non-health costs which can be misleading for decision makers aiming to make optimal use of health care budgets if there is no scope for compensation from other sectors benefiting from a given reimbursement decision.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the nationwide effects of the opioid crisis in the US, opioid illness between 2015 and 2018 cost the nation US$631 billion [ 6 ], and in 2018 cost US$93 billion to taxpayers [ 7 ]. Previous research has demonstrated the increased costs of an opioid use disorder, ranging from monetary to societal burdens like increased healthcare costs, criminal activity, and decreased productivity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%